Estudio de la evapotranspiración potencial y precipitación efectiva, para establecer requerimientos hídricos con fines de riego del cantón Catamayo. - Castillo Jaramillo, Carmen Vanessa (2024)
This study focuses on the determination of potential evapotranspiration (ETo) and effective precipitation (Pe) for efficient management of water resources in the Catamayo canton. Two databases, information from the INAMHI meteorological yearbooks and the Chelsea Climate spatial series, were used to analyze the climatic variables that influence ETo and Pe over a period of 23 years (1990-2013). Empirical methods such as Penman Monteith and simplified Hargreaves were applied, finding that the second best fits the climatic conditions of the Catamayo Valley. According to INAMHI, ETo values vary between a minimum of 4.49 mm/day in June and a maximum of 5.52 mm/day in October. Regarding CHELSEA, the values range between a of 3.13 mm/day and a of 3.82 mm/day. Regarding Pe, the values occur in May (46.32 mm) and October (45.03 mm), and the values range from November (55.36 mm) to March (119.15 mm), according to the INAMHI. For CHELSA, the months with the lowest presence of Pe are June (61.03 mm) and August (25.11 mm), and those with the highest presence range from September (116.95 mm) to March (146.12 mm). Furthermore, a Pearson correction factor was established for the two databases with an R2=0.54 using Hargreaves and 0.55 Hargreaves-Penman, showing great homogeneity in the months with the highest and lowest presence of the two components. This study provides information for the planning and sustainability of water resources in the Catamayo canton.